Features of the central nervous system lesion in patients with HIV infection in the Novosibirsk region - D. V. Kapustin; E. I. Krasnova; N. I. Khokhlova; I. P. Osipova; A. V. Totmenin; N. M. Gashnikova; O. M. Shishkova; L. L. Pozdnyakova (Лечащий Врач)
Objective. The aim of the study was to study the features of the central nervous system (CNS) lesion in patients with HIV infection in the Novosibirsk region.   Materials and methods. 204 adult patients with HIV infection were examined, hospitalized with CNS lesion, the average age was 39 ± 3.82 years. Clinical symptoms and laboratory parameters, the level of CD4+ lymphocytes were evaluated. A molecular genetic analysis of HIV-1 was carried out on the basis of the State Research Center of Virology and Biotechnology ″VECTOR″.   Results. Among 204 patients, the etiology of CNS lesion was verified in 75.6%, including CNS tuberculosis in 21.1 %, cerebral toxoplasmosis in 17.2 %. The disease was severe – 68.9 %; extremely severe with fatal outcome – in 17.5 %. The highest mortality was among patients with primary CNS lymphoma (100 %), CMV encephalitis (80 %) and PML (44.4 %). The lowest CD4+ values were observed in patients with PML (78.6 ± 30.1 cl/mcl), cryptococcal meningitis (53.8 ± 19.4 cl/mcl) and CMV encephalitis (32.8 ± 10.3 cl/mcl). Headache was more often observed in cryptococcal meningitis (100 %), motor disorders – in cerebral toxoplasmosis (94.3 %), cognitive and mental disorders – in PML (88.8 %) compared with other nosologies (p < 0.001). Inflammatory changes in the cerebrospinal fluid were more often observed in CNS tuberculosis (95.3 %) and cryptococcal meningitis (80 %), less often in cerebral toxoplasmosis (37.1 %) and PML (11.1 %), p < 0.001. Genotyping of HIV-1 in 36 patients revealed two genetic variants of the virus: subtypes CRF63_02A6 (91.7 %) and A6 (8.3 %). All patients with subtype A6 had a moderate course of the disease.   Conclusion. Secondary diseases of the central nervous system in HIV infection are more often associated with a severe degree of immunodeficiency. The established features of their manifestations contribute to early diagnosis and therapy.